Contemporary Christian spirituality: an "encompassing field" - Kourie, C.; Ruthenberg, T. (Acta Theologica, 2008)
Contemporary Christian spirituality, understood as both an experiential, lived-life phenomenon and an academic discipline gives a new-found universal perspective to the reflective Christian. It constitutes an encompassing, incorporative “field” through occupying a “give-and-take” inter-disciplinary place in a general academy of Spirituality and through repossession of its own traditions, insights and ecumenical spiritual landscape. These discoveries are further enhanced through contemporary Christian spirituality’s own critical appreciation of globalisation and postmodernism. Contemporary Christian spirituality, at its best, constitutes a world-appreciative openness that nevertheless sustains its own unique identity. In short, contemporary Christian spirituality offers a livedfaith and academic discipline that is globally conscious and universally aligned. It operates out of a credible contextual rationale for our times.